Going Beyond the Classic News Narrative Convention: The Background to and Challenges of Immersion in Journalism - Domínguez, Eva (Frontiers in Digital Humanities, 2017)
The disappearance of the screen’s physical barrier, the fourth wall, challenges many of the narrative conventions used in the traditional journalistic account. This is an area in which we are still taking the first steps, but these moves have already raised interesting narratological challenges. Technological development allows us not only to have the sensation of being elsewhere but also to interact with the storytelling elements. In this article, the author reviews the steps that have been taken up to the present time in the use of these platforms for news. She revises as well the reflections carried out by disciplines connected with narrative construction on the challenges of this new way of factual storytelling. The implications of being inside the scene of the action and being able to interact with it means rethinking the conventions of audiovisual editing and the visual perspective of the audience, as well as the relevance of the three-dimensional nature of real sound and the freedom to act inside the story without modifying the real course of the events.